Brian Bruce : new century leader - Metton, Eulalie; Viedge, Conrad ([London] : SAGE, 2016)
At the time of Brian Bruce's appointment as CEO of construction, mining, engineering and manufacturing giant Murray & Roberts, the share price had slumped 96% to 300 cents on the JSE limited. In his own words, 'the company was dying.' However, over the course of the next eight years, Bruce's leadership would result in a steady and remarkable change in the character of the group, as well as its fortunes. This book looks at how Bruce managed to turn Murray & Roberts into a viable operation once more.
Originally Published in: Metton, E., & Viedge, C. (2009). Brian Bruce - New Century Leader (Abridged). WBS-2009-2. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Bruce, Brian; Murray & Roberts (Firm); Corporate turnarounds -- Case studies